Assessing Highrise Building Construction in Semarang Using Green Construction Site Index (GCSI) - Ferry Firmawan; Hari Setijo Pudjihardjo; Diah Rahmawati (Departemen Teknik Infrastruktur Sipil Institut Teknologi Sepuluh Nopember Surabaya, 2022)
As the demand for housing increases, building construction ignore the adverse implication exposed to the environment. The objective of the study was to analyze the performance of the ongoing construction projects implementing the green construction concept. The tool applied was the Green Construction Site Index (GCSI) to assess five construction projects categorizing into three groups or specifications (uncommercialized, non-residential building; commercial, residential building; and commercial, non-residential building). The index of efficiency, productivity, and awareness upon three types of buildings was 4.06, 4.49, and 4.31 respectively. Meanwhile, the overall index obtained by the construction project type I, II, and III was 4.07, 4.33, and 4.35 respectively. The tool might be considered an opportunity to contractors; although, further investigation on its application in other types of buildings is needed.